Comparative study on the analysis of digital governance in Romania and Bulgaria - Apostol, Ana-Maria; Stan, Mari-Isabella (Technium Social Sciences Journal, 2021)
Digital government boosts countries’ economic growth and brings important benefits. This way, it involves the use of communication and information technologies by the public sector to improve the delivery of services and information by encouraging citizens to participate in the decision-making process and the holding government accountable in an effectively transparent way. Digital government offers new opportunities for more convenient and direct citizen access to government and the delivery of government services directly to citizens. This paper aims to provide an analysis of Romania and Bulgaria’s digital governance compared to the European Union, highlighting the evolution of digitisation in recent years. Although they joined the European Union at the same time, the applicability and timeliness of digital technologies differ from country to country, with Romania and Bulgaria always compared to each other in their evolution over the years.